1912 N.J. Laws 365 - (:unkn) unknown (My University, 1912)
Ch. 225, 2: A person who manufactures, or causes to be manufactured, or sells or keeps for sale, or offers, or gives, or disposes of any instrument or weapon of the kind usually known as a blackjack, slung-shot, billy, sandclub, sand-bag, bludgeon, or metal knuckles, to any person; or a person who offers, sells, loans, leases, or gives any gun, revolver, pistol or other firearm, or any air-gun, spring-gun or other instrument or weapon in which the propelling force is spring or air, or any instrument or weapon commonly known as a toy pistol or in or upon which any loaded or blank cartridges are used, or may be used, or any loaded or blank cartridges or ammunition therefor, to any person under the age of twenty-one years, is guilty of a misdemeanor;
Keywords: TRANSFER - MINORS